Clinical and imaging features of parenchymal and non-parenchymal neuro-Behçet’s disease: a systematic review of case reports and series - Omar Al-omoush; Majd M. AlBarakat; Deya’a Alasmar; Ali Al-Khalaileh; Ahmad Alzoubi; Husam Tarakhan; Zaid Shakhatreh; Zaid Hatamleh; Mohammed Abu-saleh; Othman Saleh; Abdalrahman Altiti; Wafa’ A. Hazaymeh; et al. (BMC Neurology)
Abstract Background Neuro-Behçet’s Disease (NBD) is a serious neurological complication of Behçet’s Disease, but there’s still a lack of research on its early-stage symptoms and imaging findings. While previous research highlights MRI abnormalities and cerebrospinal fluid changes, there hasn’t been a systematic effort to identify patterns specific to newly diagnosed patients. Our study aimed to investigate the clinical and imaging characteristics of newly diagnosed parenchymal and non-parenchymal NBD based on case reports and case series studies. Methods We synthesized case reports and case series from MEDLINE, Scopus, EMBASE, PubMed, Web of Science, and Cochrane Library until October 17th,2023. Multiple statistical tests, such as the chi-square and Mann-Whitney tests, were used, with the corresponding 95% confidence interval (CI). The study protocol was registered with PROSPERO (ID: CRD42023472436). We included case reports and case series of adult patients (≥ 18 years) with a confirmed diagnosis of parenchymal or non-parenchymal Neuro-Behçet’s disease (NBD), based on neurological symptoms attributed to Behçet’s disease. Studies were required to report MRI findings demonstrating central or peripheral nervous system involvement. Results Our analysis of 107 case reports and a case series (n = 174 patients) revealed that parenchymal NBD patients (n = 141; mean age 35.54 ± 13.33 years) frequently presented with ocular manifestations (80.9%), pyramidal signs (57.5%), cranial nerve palsies (50.4%), and headache (32.6%) while non-parenchymal NBD patients (n = 19; mean age 28.68 ± 10.67 years) commonly experienced headache (86.4%), papilledema (47.4%), cranial nerve palsies (42.1%), and nausea (31.6%). For the mixed-type group (n = 14; mean age 27.5 ± 11.57 years), commonly presented with headache (64.3%), pyramidal sign (50%), fever (50%), and diplopia (35.7%). Brainstem involvement for parenchymal NBD predominated in acute and chronic cases. Contrast enhancement was significantly more prevalent in acute NBD compared to chronic progressive NBD. Conclusion Neuro-Behçet’s disease is an uncommon but serious medical condition with varying symptoms based on its type. Parenchymal and non-parenchymal NBD have unique patterns, with parenchymal cases exhibiting primarily ocular symptoms and pyramidal signs, while non-parenchymal cases present with headache and papilledema. Patients with both types of features were more likely to experience headaches, pyramidal symptoms, fever, and diplopia. Recognizing these patterns can help diagnose and treat the disease earlier.